Potential spironolactone effects on collagen metabolism biomarkers in patients with uncontrolled blood pressure. Issue 4 (18th August 2018) - Ferreira, João Pedro; Rossignol, Patrick; Pizard, Anne; Machu, Jean-Loup; Collier, Timothy; Girerd, Nicolas; Huby, Anne-Cécile; Gonzalez, Arantxa; Diez, Javier; López, Begoña; Sattar, Naveed; Cleland, John G; et al.
Abstract : Background: An increase in myocardial collagen content may contribute to the development of heart failure; this might be inhibited or reversed by mineralocorticoid receptor antagonists (MRAs). We investigated changes in serum concentrations of the collagen synthesis biomarkers N-terminal propeptide of procollagen type III (PIIINP) (primary outcome) and C-terminal propeptide of procollagen type I (PICP) (secondary outcome) after non-randomised initiation of spironolactone as add-on therapy among patients with resistant hypertension enrolled in the 'Anglo-Scandinavian Cardiac Outcomes' trial (ASCOT). Methods: An age/sex matching plus propensity-scored logistic regression model incorporating variables related to the outcome and spironolactone treatment was created to compare patients treated with spironolactone for a 9-month period versus matched controls. A within-person analysis comparing changes in serum biomarker concentrations in the 9 months before versus after spironolactone treatment was also performed. Results: Patients included in the between-person analysis (n=146) were well matched: the mean age was 63±7 years and 11% were woman. Serum concentrations of PIIINP and PICP rose in 'controls' and fell during spironolactone treatment (adjusted means +0.52 (−0.05 to 1.09) vs −0.41 (−0.97 to 0.16) ng/mL, p=0.031 for PIIINP and +4.54(−1.77 to 10.9) vs −6.36 (−12.5 to −0.21) ng/mL, p=0.023 for PICP). For the within-person analysis (n=173), spironolactone treatment was also associated with a reduction in PICP (beta estimate=−11.82(−17.53 to −6.10) ng/mL, p<0.001) but not in PIIINP levels. Conclusions: Treatment with spironolactone was associated with a reduction in serum biomarkers of collagen synthesis independently of blood pressure in patients with hypertension, suggesting that spironolactone might exert favourable effects on myocardial collagen synthesis and fibrosis. Whether this effect might contribute to slowing the progression to heart failure is worth investigating.